Designing and implementing test automation frameworks with QTP learn how to design and implement a test automation framework block by block - Bhargava, Ashish (Birmingham : Packt Publishing, 2013)
A tutorial-based approach, showing basic coding and designing techniques to build test automation frameworks. If you are a beginner, an automation engineer, an aspiring test automation engineer, a manual tester, a test lead or a test architect who wants to learn, create, and maintain test automation frameworks, this book will accelerate your ability to develop and adapt the framework.
Adding examples of expressionsControl structures and loops; Using loops; The Do Loop; Introducing frameworks; The automation framework and types of framework; Record and replay; Advantages and disadvantages of linear a framework; Introduction to the data-driven framework; The FileSystemObject object model; Introduction to the modular framework; Structure; Advantages; Design; High cohesion and coupling; Decreasing coupling and increasing cohesion; Analyzing the application; Creating a design; Setting up an environment; Creating Object Repository; Creating test-level components.
Creating script-level functions.
Includes index.
Print version record.
Master record variable field(s) change: 050, 072, 082
Keywords: Application software -- Testing -- Computer programs; Computer software -- Testing -- Computer programs; COMPUTERS / Software Development & Engineering / Quality Assurance & Testing; Computer science; Database management; Microsoft frameworks; Electronic books